Biosensors Based on Sandwich Assays (Springer Singapore, 2018)
This book shows the various sandwich assays that are constructed from recognition molecules, such as antibodies, oligonucleotide sequences and aptamers, developed as a result of nano- and biotechnology advances. It consists of ten chapters presenting interesting examples of these assays, organized according to the type of analytic methods (colorimetric, fluorescence, electrochemical, etc.) and detected objects (protein, nucleic acid, small-molecule, ion, etc.). It also includes a chapter discussing the introduction of sandwich assays as biosensors for the detection of a range of targets. It is an interesting and useful resource for a wide readership in various fields of chemical science and nanotechnology.